Calibration of Water Inrush Channel and Numerical Simulation of Water Inrush Process in Coal Mine Roof - Sun, Dongdong; Hou, Xiangang; Yang, Tianhong; Zhao, Yong; Zhang, Penghai; Yang, Bin; Liu, Yilong; Ma, Ka (Frontiers in Earth Science, 2022)
The surrounding rock of a coal mine roof fractures with the excavation of the underground working face in coal mining. These mining-induced fractures are connected and extended upward to form water inrush channels. A water inrush accident may occur when there is a sufficiently large water source. To elucidate the formation mechanisms of the roof water inrush channel and the characteristics of water inrush in goafs, we performed a case study of No.18401 Panel of Xiqu Coal Mine in China and determined whether the roof water inrush channel is connected by theoretical calculation and microseismic monitoring. The modified mechanical parameters of rock masses were embedded into the numerical model based on microseismic data. Microseismic monitoring and numerical simulation were organically combined to analyze the connection process of the water inrush channel, after which the roof water inrush channel is calibrated on the No.18401 Panel. We established a non-Darcy flow model for water inrush in the water-conducting fractured zone of mines by coupling the Darcy, Forchheimer, and Navier–Stokes equations. Finite element language and its compiler (FELAC) was used to study the water inrush mechanism of non-Darcy seepage. The results show that the pressure, velocity, and porosity in the water-conducting fractured zone are non-uniform in water inrush occurrence and development, and the mixed fluid mainly passes through the “dominant channel.” The development of water inrush is accompanied by the release of the hydrostatic pressure in the aquifer, the sudden increase of the velocity at the water inrush position, and the increase in fluid concentration. Hence, the underground water inrush can be predicted and prevented by monitoring the aforementioned indicators. This research is of great significance for the calibration of the water inrush channel of the roof and the prediction of water inrush disasters.